The 3'tsRNAs are aminoacylated: Implications for their biogenesis. - Ziwei Liu (Public Library of Science (PLoS), 2021)
Emerging evidence indicates that tRNA-derived small RNAs (tsRNAs) are involved in fine-tuning gene expression and become dysregulated in various cancers. We recently showed that the 22nt LeuCAG3´tsRNA from the 3´ end of tRNALeu is required for efficient translation of a ribosomal protein mRNA and ribosome biogenesis. Inactivation of this 3´tsRNA induced apoptosis in rapidly dividing cells and suppressed the growth of a patient-derived orthotopic hepatocellular carcinoma in mice. The mechanism involved in the generation of the 3´tsRNAs remains elusive and it is unclear if the 3´-ends of 3´tsRNAs are aminoacylated. Here we report an enzymatic method utilizing exonuclease T to determine the 3´charging status of tRNAs and tsRNAs. Our results showed that the LeuCAG3´tsRNA, and two other 3´tsRNAs are fully aminoacylated. When the leucyl-tRNA synthetase (LARS1) was inhibited, there was no change in the total tRNALeu concentration but a reduction in both the charged tRNALeu and LeuCAG3´tsRNA, suggesting the 3´tsRNAs are fully charged and originated solely from the charged mature tRNA. Altering LARS1 expression or the expression of various tRNALeu mutants were also shown to affect the generation of the LeuCAG3´tsRNA further suggesting they are created in a highly regulated process. The fact that the 3´tsRNAs are aminoacylated and their production is regulated provides additional insights into their importance in post-transcriptional gene regulation that includes coordinating the production of the protein synthetic machinery.